Find sum of all real x such that the below equation is true. 9 x − 4 ⋅ 3 x + 6 − 3 x 4 + 9 x 1 = 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
9 x − 4 ⋅ 3 x + 6 − 3 x 4 + 9 x 1 9 − x ( 3 x − 1 ) 4 = 0 = 0
9 − x = 0 is impossible. Since we're searching real value of x , there's no x that satisfy the equation.
So the only possible solution is 3 x − 1 = 0 . Hence x = 0 .
Problem Loading...
Note Loading...
Set Loading...
Put 3 x = t and 9 x = t 2 so that equation simplifies to:
t 2 − 4 t + 6 − t 4 + t 2 1 = 0 ⟺ ( t 2 + t 2 1 ) − 4 ( t + t 1 ) + 6 = 0 ⟺ ( t + t 1 ) 2 − 4 ( t + t 1 ) + 4 = 0 ⟺ ( t + t 1 − 2 ) 2 = 0 t + t 1 = 2 ⟺ t = 3 x = 1 ⟺ x = 0 (Since t + t 1 ≥ 2 ∀ t ≥ 0 )